Combined Use of N-Palmitoyl-Glycine-Histidine Gel and Several Penetration Enhancers on the Skin Permeation and Concentration of Metronidazole - Sabrina Dahlizar; Mika Futaki; Akie Okada; Chihiro Yatomi; Hiroaki Todo; Kenji Sugibayashi (MDPI AG, 2018)
N-Palmitoyl-Glycine-Histidine (Pal-GH) is a novel low molecular weight gelator. In our previous report, ivermectin, a lipophilic drug, was effectively delivered to skin tissue after topical application with Pal-GH as a spray gel formulation, and a much higher skin concentration was confirmed than with the administration of a conventional oral formulation. The objective of this study was to increase the skin permeation of metronidazole (MTZ), a hydrophilic drug, after the topical application of Pal-GH gel. An evaluation of the combined effect of chemical penetration enhancers (CPEs), such as isopropyl myristate (IPM), propylene glycol (PG), ethanol, diethylene glycol monoethyl ether, and dimethyl sulfoxide (DMSO), on skin permeation was also conducted. We found that a 5% Pal-GH gel containing 1% MTZ (F5MTZ) exhibited a 2.7-fold higher MTZ permeation through excised hairless rat skin than its solution. Furthermore, F5PG-MTZ and F5IPM-MTZ further increased the skin permeation of MTZ when compared to F5MTZ. Interestingly, F5PG-MTZ enhanced the skin penetration of MTZ, although no enhancement effect was observed for an MTZ solution containing PG. Thus, a Pal-GH formulation containing PG and IPM may enhance the skin permeation of MTZ.